A Socio-Ecological Framework for Cancer Prevention in Low and Middle-Income Countries - Akinyemiju, Tomi; Ogunsina, Kemi; Gupta, Anjali; Liu, Iris; Braithwaite, Dejana; Hiatt, Robert A. (Frontiers in Public Health, 2022)
Cancer incidence and mortality rates continue to rise globally, a trend mostly driven by preventable cancers occurring in low-and middle-income countries (LMICs). There is growing concern that many LMICs are ill-equipped to cope with markedly increased burden of cancer due to lack of comprehensive cancer control programs that incorporate primary, secondary, and tertiary prevention strategies. Notably, few countries have allocated budgets to implement such programs. In this review, we utilize a socio-ecological framework to summarize primary (risk reduction), secondary (early detection), and tertiary (treatment and survivorship) strategies to reduce the cancer burden in these countries across the individual, organizational, community, and policy levels. We highlight strategies that center on promoting health behaviors and reducing cancer risk, including diet, tobacco, alcohol, and vaccine uptake, approaches to promote routine cancer screenings, and policies to support comprehensive cancer treatment. Consistent with goals promulgated by the United Nations General Assembly on Noncommunicable Disease Prevention and Control, our review supports the development and implementation of sustainable national comprehensive cancer control plans in partnership with local communities to enhance cultural relevance and adoption, incorporating strategies across the socio-ecological framework. Such a concerted commitment will be necessary to curtail the rising cancer and chronic disease burden in LMICs.